2012
DOI: 10.1016/j.joca.2012.02.639
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss is effective for symptomatic relief in obese subjects with knee osteoarthritis independently of joint damage severity assessed by high-field MRI and radiography

Abstract: Presence of joint damage did not preclude symptomatic relief following a clinically relevant weight loss in older obese patients with KOA. Neither muscle strength nor knee-joint alignment was associated with the degree of symptomatic relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 60 publications
2
58
1
5
Order By: Relevance
“…There were 23 variables investigated as possible predictors of response to the weight loss programs, including measurements of baseline hamstrings and quadriceps strength using isometric dynamometry. Baseline muscle strength was not predictive of symptomatic relief in response to the weight loss program (46). The study was underpowered to detect significant predictors from a possible 23 variables.…”
Section: Muscle Strengthmentioning
confidence: 90%
See 3 more Smart Citations
“…There were 23 variables investigated as possible predictors of response to the weight loss programs, including measurements of baseline hamstrings and quadriceps strength using isometric dynamometry. Baseline muscle strength was not predictive of symptomatic relief in response to the weight loss program (46). The study was underpowered to detect significant predictors from a possible 23 variables.…”
Section: Muscle Strengthmentioning
confidence: 90%
“…In contrast the two other studies categorized subjects to knee malalignment groups if the mechanical axis did not appear as a straight line (46,49). This may have increased the severity of malalignment observed within the participants assigned to the varus group investigated by Lim and colleagues, compared to the subjects categorized to knee malalignment groups in the other studies.…”
Section: Muscle Strengthmentioning
confidence: 94%
See 2 more Smart Citations
“…In trials among subjects with and without established knee OA, weight loss was shown to have advantageous structure-modifying, systemic, and clinical effects (15)(16)(17)(18)(19)(20)(21). In a systematic review on the effects of weight loss on knee OA patients, a weight loss of at least 5% of body weight was indicated for symptomatic relief (22).…”
Section: Introductionmentioning
confidence: 99%